Domestic Investment Laws, International Economic Law, and Economic Development. Issue 1 (February 2023) - Olaoye, Kehinde Folake; Sornarajah, Muthucumaraswamy
Abstract: 'Development' is a legal concept which has been central to the practice of international economic law (IEL). This Article examines how 'development' continues to be at the heart of struggles between domestic investment laws (DILs) and international economic law. By examining over 3000 international investment agreements (IIAs) and DILs signed in the last seven decades, this Article identifies the ways in which the concept of development has evolved in tandem with the growth of international economic law by dividing the history of international investment law into six main phases. It traces the emergence of 'development' in DIL to the decolonization era arguing that post 1990, the proliferation of international investment treaties and growth of investment treaty arbitration have been used as tools of liberalization on the weak premise that this would lead to economic development. In this context, this Article examines closely the interpretation of 'investment' by ICSID tribunals, promotion of international arbitration for economic development, attempts to internationalize economic development contracts, continued relevance of the New International Economic Order, and shift to sustainable development in IEL discourse.